Characterization of the Binding of Bovine Thrombin to Isolated Rat Hepatocytes - Weyer, Britta; Petersen, Torben E; Sonne, Ole (Thrombosis and Haemostasis, 1988)
Isolated rat hepatocytes possess per cell 4,500 high-affinity binding sites for thrombin with a Kd of 30-40 pM, and 2.8 × 105 low-affinity sites with a Kd of 30 nM. These binding sites are highly specific for thrombin. Half-maximal binding of 125I-labelled thrombin is achieved after 3 min at 37¸ C and 7 min at 4¸ C. The reversibly bound fraction of the ligand dissociates according to a biexponential time course with the rate constants 1—2 × 10−2 s−1 and 3—4 × 10−4 s−1. Part of the tracer remains cell-associated even after prolonged incubation, but all cell-associated radioactivity migrates as intact thrombin upon sodium dodecyl sulphate polyacrylamide gel electrophoresis. The bound thrombin is minimally endocytosed as judged by the resistance to pH 3-treatment. Cell-associated radioactivity dissociated from the cells binds just aswell in a receptor assay as tracer incubated in a conditioned medium under the same conditions, indicating the absence of a quantitatively important receptor-mediated degradation ofthe ligand.
Keywords: Thrombin; Receptor; Thrombin; binding site; High; affinity; binding; Rat hepatocyte